Chain Hanging Over a Table

There is a chain of uniform density on a table with negligible friction. The length of the entire chain is 1 m \si{1\ \meter} . Initially, one-third of the chain is hanging over the edge of the table. How long will it take the chain (in seconds) to slide off the table?

Take g = 9.8 m / s 2 g = 9.8 \si{ m/s^2} .


The answer is 0.563.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Steven Zheng
Sep 14, 2014

The solution to this problem requires us to solve differential equations.

We begin with first principles (in Newtonian Mechanics). F n e t = a c c e l e r a t e d m a s s × a {F}_{net} = accelerated\quad mass \times a

Let l l be the length of the chain, and x x be the variable length hanging over the edge of the table. Since the mass is uniformly dense, we let ρ \rho be the density. Hence,

( ρ x ) g = ( ρ l ) d v d t (\rho x) g = (\rho l) \frac{dv}{dt}

Since d v d t = d v d x d x d t = v d v d x \frac{dv}{dt} = \frac{dv}{dx} \frac{dx}{dt} = v\frac{dv}{dx} , we can rewrite the above equation as

v d v d x = g x l v\frac{dv}{dx} = \frac{gx}{l}

Let h h be the initial length hanging over the edge of the table. We solve the above differential equation when v = 0 v =0 (before sliding).

v 2 = g l ( x 2 h 2 ) {v}^{2} = \frac{g}{l} ({x}^{2} - {h}^{2}) v = g l ( x 2 h 2 ) v = \sqrt{\frac{g}{l} ({x}^{2} - {h}^{2})}

Now we let v = d x d t v = \frac{dx}{dt} and solve the new differential equation at x = h x = h at the initial time t = 0 t=0 . (I searched up this integral.)

l n ( x + x 2 h 2 h ) = g l t ln\left(\frac{x+\sqrt{{x}^{2} - {h}^{2}}}{h}\right) = \sqrt{\frac{g}{l}}t

The chain slides off the table at x = l x=l so we get t = l g l n ( l + l 2 h 2 h ) . t = \sqrt{\frac{l}{g}}ln\left(\frac{l+\sqrt{{l}^{2} - {h}^{2}}}{h}\right).

Plugging in the values h = 1 / 3 , l = 1 , g = 9.8 h=1/3, l=1, g = 9.8 we get t = 0.563 s e c o n d s t = 0.563 seconds .

Looks good, Steven. I wasn't able to see the comment that you left for me on your previous post since the question was deleted, but no matter. As for this version, when I saw that you reposted I quickly pressed the "Reveal 1 solution" box without first putting in my answer! ... facepalm ... Oh well. It's a good question so I'll re-share it. :)

Brian Charlesworth - 6 years, 9 months ago

Log in to reply

You were right. I made a stupid mistake thinking that there was something wrong with my solution. The original problem had the correct answer, but nobody seemed to have solved it, so I thought that I forgot to subtract 1/3 from 1, without reviewing the equation ( ρ x ) g = ( ρ l ) d v d t . (\rho x) g = (\rho l) \frac{dv}{dt}.

This is my third post of the question.

Steven Zheng - 6 years, 9 months ago

Log in to reply

Oh, I see. Yes, I've posted a few questions that others, initially, weren't solving, which made me wonder if I had posted the correct answer, so I know how that feels. Anyway, now, if nobody is solving the question then you know that it's just because it's a tough question to solve; there aren't that many questions on this site that require an application of differential equations.

Brian Charlesworth - 6 years, 9 months ago

Hmm i got 0.55 and it was wrong :( I used substitution that: x/h = cosh(p) and integral become just dp :)

Вук Радовић - 6 years, 5 months ago

This could also be solved by energy conservation method which would indeed make it much more simplified.

Siddharth Dhawan - 6 years, 8 months ago

Log in to reply

Can you present a solution with the conservation of energy?

Steven Zheng - 6 years, 8 months ago
Satvik Pandey
Oct 1, 2014

I will solve it with conservation of energy. Let x denote the vertical coordinate of the chain's free end. As the chains free end is at distance x so the CoM of chain will be at a distance* x/2*.

So * M ( x ) = M L x M(x)=\frac { M }{ L } x *

and U ( x ) = M x 2 g 2 L U(x)=-\frac { M{ x }^{ 2 } g}{ 2L }

As K i + U i = K f + U f { K }_{ i }+{ U }_{ i }={ K }_{ f }+{ U }_{ f }

So 0 m g 18 = m v 2 2 + m x 2 g 2 0-\frac { mg }{ 18 } =\frac { m{ v }^{ 2 } }{ 2 } +\frac { -m{ { x }^{ 2 } }g }{ 2 }

or m v 2 2 = m x 2 g 2 m g 18 \frac { m{ v }^{ 2 } }{ 2 } =\frac { m{ x }^{ 2 }g }{ 2 } -\frac { mg }{ 18 }

or m v 2 2 = 9 m x 2 g m g 18 \frac { m{ v }^{ 2 } }{ 2 } =\frac { 9{ mx }^{ 2 }g-mg }{ 18 }

or 9 v 2 = ( 9 x 2 1 ) g 9{ v }^{ 2 }=(9{ x }^{ 2 }-1)g

or d t d x = 9 ( 9 x 2 1 ) g \frac { dt }{ dx } =\sqrt { \frac { 9 }{ (9{ x }^{ 2 }-1)g } }

or d t = 9 ( 9 x 2 1 ) g d x dt=\sqrt { \frac { 9 }{ (9{ x }^{ 2 }-1)g } } dx

or 0 t d t = 1 3 1 9 ( 9 x 2 1 ) g d x \int _{ 0 }^{ t }{ dt } =\int _{ \frac { 1 }{ 3 } }^{ 1 }{ \sqrt { \frac { 9 }{ (9{ x }^{ 2 }-1)g } } dx }

or t = 3 g 1 3 1 1 ( 9 x 2 1 ) d x t=\frac { 3 }{ \sqrt { g } } \int _{ \frac { 1 }{ 3 } }^{ 1 }{ \sqrt { \frac { 1 }{ (9{ x }^{ 2 }-1) } } } dx

or t = 3 g 1 3 1 1 9 ( x 2 1 9 ) d x t=\frac { 3 }{ \sqrt { g } } \int _{ \frac { 1 }{ 3 } }^{ 1 }{ \sqrt { \frac { 1 }{ 9\left( { x }^{ 2 }-\frac { 1 }{ 9 } \right) } } } dx

or t = 1 g 1 3 1 1 ( x 2 1 9 ) d x t=\frac { 1 }{ \sqrt { g } } \int _{ \frac { 1 }{ 3 } }^{ 1 }{ \sqrt { \frac { 1 }{ \left( { x }^{ 2 }-\frac { 1 }{ 9 } \right) } } dx }

or t = 1 g log x + x 2 1 9 t=\frac { 1 }{ \sqrt { g } } \log { \left| x+\sqrt { { x }^{ 2 }-\frac { 1 }{ 9 } } \right| }

or t = 1 g log 3 x + 9 x 2 1 3 t=\frac { 1 }{ \sqrt { g } } \log { \left| \frac { 3x+\sqrt { 9{ x }^{ 2 }-1 } }{ 3 } \right| } where limits are - lower limit is 1/3 and upper limit is 1

or f r a c 1 g { log 3 + 2 2 3 log 1 3 } frac { 1 }{ \sqrt { g } } \left\{ \log { \left| \frac { 3+2\sqrt { 2 } }{ 3 } \right| } -\log { \left| \frac { 1 }{ 3 } \right| } \right\}

or 1 g { log 1.94 log 0.33 } \frac { 1 }{ \sqrt { g } } \left\{ \log { \left| 1.94 \right| } -\log { \left| 0.33 \right| } \right\}

or 1 g { 0.28 ( 0.48 ) } \frac { 1 }{ \sqrt { g } } \left\{ 0.28-(-0.48) \right\} =0.243

By multiplying this 2.303 (to convert common logarithms into natural logarithms) we will get the answers.

2.303(0.243)=0.566 sec

In 3rd last line consider f r a c 1 g frac1\sqrt { g } as 1 g \frac { 1 }{ \sqrt { g } } .

satvik pandey - 6 years, 8 months ago

Log in to reply

thanks @satvik pandey nice solution a one i could understand, you are so good at physics can you recommenced anything

Mardokay Mosazghi - 6 years, 8 months ago

Log in to reply

Thank you Mardokay. I am not so 'good' at physics I think I am little more than descent. :D

I recommend you to practice more and more question of physics as 'practice makes a man perfect'. :)

satvik pandey - 6 years, 8 months ago

Please reply @satvik. In the energy conservation , what is m? If u took m=M/L, shouldn't 1/2mv² be1/2mv²x

Ashwin Gopal - 6 years, 4 months ago
Milly Choochoo
Sep 25, 2014

This problem can be solved very easily with a little bit of knowledge of differential equations (or wolframalpha to do the job if you don't!).

If you do a bit of elementary mechanics (free-body diagram analysis) on the initial conditions given, the acceleration of the entire string at the beginning is 1 3 g \frac{1}{3}g , with the 1 3 \frac{1}{3} coming from the fraction of the string hanging off the edge. With this, a nifty re-illustration of the problem can be made.

Imgur Imgur

So we have an extremely simple second order differential equation

x ( t ) = g x ( t ) x''(t) = gx(t)

with the initial conditions x ( 0 ) = 1 3 x(0)=\frac{1}{3} and x ( 0 ) = 0 x'(0) = 0 . The most general solution to the differential equations is

x ( t ) = c 1 e g t + c 2 e g t x(t) = c_1e^{\sqrt{g}t} + c_2e^{-\sqrt{g}t}

and plugging in the initial conditions gives us the solution,

x ( t ) = 1 6 ( e g t + e g t ) x(t) = \frac{1}{6}(e^{\sqrt{g}t} + e^{-\sqrt{g}t} )

Now we set x = 1 x=1 , and solve for t t .

t . 563 t\approx.563

Debarya Das
May 22, 2016

Let l l be the length of the chain, and x x be the variable length hanging over the edge of the table.

initially x=1/3 m

By energy conservation

1 2 m v 2 = m g x 2 l m g 9 \frac { 1 }{ 2 } { mv }^{ 2 }=\frac { m{ g }x^{ 2 } }{ l } -\frac { mg }{ 9 }

Putting l=1 m, velocity at an instant is given by

v = g x 2 g 9 v=\sqrt { g{ x }^{ 2 }-\frac { g }{ 9 } }

Since v = d x d t v=\frac { dx }{ dt }

Putting value of v v

d x d t = g x 2 g 9 \quad \frac { dx }{ dt } =\sqrt { g{ x }^{ 2 }-\frac { g }{ 9 } }

d x g x 2 g 9 = d t \frac { dx }{ \sqrt { g{ x }^{ 2 }-\frac { g }{ 9 } } } =\quad dt

Integrating LHS from x = 1 3 x=\frac { 1 }{ 3 } to x = 1 x=1 and RHS from t = 0 t=0 to t = t t=t

1 3 1 d x x 2 1 9 = g 0 t d t \int _{ \frac { 1 }{ 3 } }^{ 1 }{ \frac { dx }{ \sqrt { { x }^{ 2 }-\frac { 1 }{ 9 } } } } =\quad \sqrt { g } \int _{ 0 }^{ t }{ dt }

[ l n ( x + x 2 1 9 ) ] 1 3 1 g = t \frac { [ln(x+\sqrt { { x }^{ 2 }-\frac { 1 }{ 9 } } ){ ] }_{ \frac { 1 }{ 3 } }^{ 1 } }{ \sqrt { g } } =t

Putting g=9.8

t = l n ( 3 + 8 ) 9.8 t=\frac { ln(3+\sqrt { 8 } ) }{ \sqrt { 9.8 } }

Therefore t = 0.557 \boxed { t=0.557 }

Vinay Agarwal
Jan 28, 2015

It's really a beautyful problem.Keep uploading such problems

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...